2018
DOI: 10.1002/jper.17-0491
|View full text |Cite
|
Sign up to set email alerts
|

A comparative, randomized, prospective, two‐center clinical study to evaluate the clinical and esthetic outcomes of two different bone grafting techniques in early implant placement

Abstract: Background Early implant placement combined with simultaneous contour augmentation was able to rebuild stable facial hard‐tissue and soft‐tissue contours that were esthetically pleasing. The purpose of this study was to evaluate the clinical esthetic outcome, when two different bone grafting materials were used. Methods Forty‐eight patients were randomly assigned into two groups. In the control group, autogenous bone was used to cover the exposed implant surface then a layer of deproteinized bovine bone minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Nevertheless, also in this trial only 3 out of 28 dehiscencies were fully covered at re-entry and abutment connection. authors concluded both grafts offered good results in terms of contour augmentation (Mau et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, also in this trial only 3 out of 28 dehiscencies were fully covered at re-entry and abutment connection. authors concluded both grafts offered good results in terms of contour augmentation (Mau et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…Peri‐apical radiographs were used to assess marginal bone level alterations, and clinical parameters were recorded. The authors concluded both grafts offered good results in terms of contour augmentation (Mau et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Reason for Exclusion Aghazadeh et al, 2012 [140] Application of granular autograft Arenaz-Búa et al, 2010 [141] Application of granular autograft Barboza et al, 2010 [142] Application of allogeneic bone granules Beitlitum et al, 2018 [143] Application of allogeneic bone granules Bianconi et al, 2017 [144] Alveolar ridge preservation Charde et al, 2020 [145] Block used for peri-implant bone regeneration Naishlos et al, 2021 [146] Blocks used for sinus floor augmentation Corinaldesi et al, 2009 [147] Application of autogenous bone granules El Chaar et al, 2019 [148] Application of allogeneic bone granules Ge et al, 2017 [149] Application of granular autograft Güven and Tekin, 2006 [150] Wrong indication (cyst filling) Huang et al, 2016 [151] Application of allogeneic bone granules Ilankovan et al, 1998 [152] No outcome of interest reported Jacotti et al, 2012 [153] Sample size too small Kang et al, 2015 [154] Particulated iliac bone applied with sinus lift Khoury and Hanser, 2015 [155] No outcome of interest reported Krasny et al, 2018 [156] Inclusion of patients with follow-up of less than 12 months Lekholm et al, 1999 [157] Application of different surgical approaches, missing patient information [160] Application of granular materials Merli et al, 2020 [161] Application of granular grafting materials Morad and Khojasteh, 2013 [162] Sample size too small Mordenfeld et al, 2017 [163] Application of granular autograft Özkan et al, 2007 [164] Sample size too small Pimentel et al, 2014 [165] Sample size too small Putters et al, 2018 [166] No outcome of interest reported Quereshy et al, 2010 [167] Sample size too small Sethi et al, 2020 [168] Inclusion of patients with follow-up < 12 months Simion et al, 2001 [169] Application of granular materials Simon et al, 2000 [170] Surgical technique (ARP) Soehardi et al, 2009 [171] No differentiation between onlay block and sinus floor elevation Solakoglu et al, 2019 …”
Section: Studymentioning
confidence: 99%
“…Because limited sites were treated by FDBA, the statistical significance of FDBA relative to other BRGs was not achievable. Based on equivalent regeneration outcomes of FDBA and DBBM in the alveolar ridge and sinus augmentation [28,29], a similar regeneration capability of FDBA and DBBM in furcation defects could be expected.…”
Section: Discussionmentioning
confidence: 96%